Community Mediation in Islamic Inheritance Disputes: Integrating Sulh and Syahrur's Theory of Limits in The Suralaga Community - Asmuni Asmuni; Nasri Nasri (MUSLIM HERITAGE, 2026)
The distribution of inheritance is one of the key aspects of Islamic family law that frequently gives rise to disputes. Consequently, this study aims to identify an integrative model for dispute resolution through community mediation, drawing on Muhammad Syahrur’s theory of limits. The study employs a normative empirical method with a socio legal approach that combines the study of Islamic law, customary law, and empirical data. Data was obtained through interviews with customary leaders, religious leaders, and mediators. The results of the study indicate that community mediation through the sulh mechanism integrates Islamic values, customary law, and state law. In this process, religious and customary leaders act as mediators who promote peace, justice, and agreement among the parties. Based on Muhammad Syahrur’s theory of limits, this allows for flexibility in determining inheritance shares, taking into account minimum and maximum limits in accordance with the socio-cultural context of the community without contravening the principles of Sharia. The integration of Islamic norms, the theory of limits, and the practice of sulh produces a restorative, participatory, and contextual model of dispute resolution, gaining both socio cultural legitimacy and legal legitimacy through formal legal recognition. Thus, this integrative model is not only an effective alternative for dispute resolution but also a new paradigm for achieving fair inheritance dispute resolution through the synergy between religion, custom, and state law.   Abstrak Pembagian harta waris merupakan salah satu aspek penting dalam hukum keluarga Islam yang kerap menimbulkan sengketa. Untuk itu penelitian ini bertujuan menemukan model integratif penyelesaian sengketa melalui mediasi komunitas perspektif teori limit Muhammad Syahrur. Penelitian ini menggunakan metode normatif empiris dengan pendekatan sosio legal yang menggabungkan kajian hukum Islam, hukum adat, dan data empiris. Data diperoleh melalui wawancara dengan tokoh adat, tokoh agama, dan mediator. Hasil penelitian menunjukkan mediasi komunitas melalui mekanisme suluh mengintegrasikan nilai Islam, adat, dan hukum negara. Dalam proses ini, tokoh agama dan tokoh adat berperan sebagai mediator yang mendorong perdamaian, keadilan, dan kesepakatan para pihak. Berdasarkan teori limit Muhammad Syahrur memungkinkan fleksibilitas dalam menentukan bagian waris, dengan mempertimbangkan batas minimal dan maksimal sesuai konteks sosio kultural masyarakat tanpa menyalahi prinsip syariat. Integrasi antara norma Islam, teori limit, dan praktik suluh menghasilkan model penyelesaian sengketa yang restoratif, partisipatif, dan kontekstual serta memperoleh legitimasi secara sosio kultural dan legitimasi yuridis melalui pengakuan hukum formal. Dengan demikian model integratif ini tidak hanya menjadi alternatif penyelesaian sengketa yang efektif, tetapi juga menjadi paradigma baru untuk mewujudkan penyelesaian sengketa waris yang berkeadilan melalui sinergi antara agama, adat, dan hukum negara